2013
DOI: 10.3762/bjoc.9.90
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the σ-complex stability for quantifying reactivity in nucleophilic substitution of aromatic fluorides

Abstract: SummaryA computational approach using density functional theory to compute the energies of the possible σ-complex reaction intermediates, the “σ-complex approach”, has been shown to be very useful in predicting regioselectivity, in electrophilic as well as nucleophilic aromatic substitution. In this article we give a short overview of the background for these investigations and the general requirements for predictive reactivity models for the pharmaceutical industry. We also present new results regarding the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
1
32
0
2
Order By: Relevance
“…In an earlier article concerning nucleophilic aromatic substitution reactions (with fluorine as the leaving group) we have also identified the geometric and energetic resemblance between the σ-complex reaction intermediate and the rate-determining transition state as the reason for the excellent correlations between the energies for forming the σ-complex and the experimentally found reaction rate (measured both as correlation coefficient and as MAD) [ 31 ]. Thus, both S N Ar as well as S E Ar nitrations and S E Ar halogenations constitute instructive examples if we want to formulate a more efficient approach to investigate whether a simplified reactivity model, based on the energy of the highest reaction intermediate, is likely to be a useful approximation.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier article concerning nucleophilic aromatic substitution reactions (with fluorine as the leaving group) we have also identified the geometric and energetic resemblance between the σ-complex reaction intermediate and the rate-determining transition state as the reason for the excellent correlations between the energies for forming the σ-complex and the experimentally found reaction rate (measured both as correlation coefficient and as MAD) [ 31 ]. Thus, both S N Ar as well as S E Ar nitrations and S E Ar halogenations constitute instructive examples if we want to formulate a more efficient approach to investigate whether a simplified reactivity model, based on the energy of the highest reaction intermediate, is likely to be a useful approximation.…”
Section: Resultsmentioning
confidence: 99%
“…Einem früheren Modell zur Bestimmung der Substitutionsposition in Pentafluoraromaten folgend, unternahmen Brink und ein AstraZeneca‐Team mit Svensson, Liljenberg et al . Vorhersagen der Regioselektivität von S N Ar‐Reaktionen basierend auf der Stabilität des Meisenheimer‐Intermediats.…”
Section: Beiträge Aus Der Quantenchemieunclassified
“…The question of whether the Meisenheimer s-complex is a stable minimum or a transition state along the reaction coordinate of the S N Ar reaction, that is, whether the reaction is stepwise or concerted, has been addressed in a number of previous computational studies ( Figure 5). [50][51][52][53][54][55][56] The answer depends on the nature of the nucleophile (neutral/anionic, nucleophilicity), the leaving group (bond strength, stability of free leaving group), the arene core (substitution pattern), and the reaction medium (gas phase, solvent polarity). For reactions of fluoroarenes (mostly fluorobenzenes) with various nucleophiles, the s-complex was in most cases found to be an intermediate, [50][51][52][53] only two studies reported it to be a transition state: in the reaction of para-NO 2 C 6 H 4 F with NH 3 or NH 2 Me [50] and in the reaction of C 6 H 5 F with Me 2 NSiMe 3 or Me 2 PSiMe 3 .…”
Section: Computational Mechanistic Studymentioning
confidence: 99%
“…[50][51][52][53][54][55][56] The answer depends on the nature of the nucleophile (neutral/anionic, nucleophilicity), the leaving group (bond strength, stability of free leaving group), the arene core (substitution pattern), and the reaction medium (gas phase, solvent polarity). For reactions of fluoroarenes (mostly fluorobenzenes) with various nucleophiles, the s-complex was in most cases found to be an intermediate, [50][51][52][53] only two studies reported it to be a transition state: in the reaction of para-NO 2 C 6 H 4 F with NH 3 or NH 2 Me [50] and in the reaction of C 6 H 5 F with Me 2 NSiMe 3 or Me 2 PSiMe 3 . [54] Both cases are special in that the departing fluoride can bind to the nucleophile (hydrogen bonding in the former, formation of a fluorosilane in the latter) and is therefore greatly stabilised, despite both reactions being in vacuum.…”
Section: Computational Mechanistic Studymentioning
confidence: 99%